Progressive length‐dependent polyneuropathy in xeroderma pigmentosum group A. Issue 4 (10th August 2020) - Tsuji, Yukio; Ueda, Takehiro; Sekiguchi, Kenji; Nishiyama, Masahiro; Kanda, Fumio; Nishigori, Chikako; Toda, Tatsushi; Matsumoto, Riki
Abstract: Background: In this study, we aimed to investigate the progression of peripheral nervous system involvement in xeroderma pigmentosum group A (XP‐A). Methods: We performed nerve conduction studies in 17 genetically confirmed XP‐A patients and conducted follow‐ups. Of these patients we also analyzed gray matter volume (GMV) using brain MRI and assessed the severity score of clinical and skin manifestation. Results: We found significant reduction in the motor and sensory nerve action potential amplitude and mild reduction in conduction velocity. These findings were predominant in sensory nerves and the lower limbs, were observed since early childhood, and gradually deteriorated with age. Conclusions: The electrophysiological characteristics of XP‐A patients are consistent with length‐dependent axonal polyneuropathy and there is progressive deterioration from early childhood.